Geochemical characteristics of weathering crusts on the Dzhezhimparma Ridge and the Nemskaya Upland (South Timan) - Oksana V. Grakova; Nataliya Yu. Nikulova; Yuliya S. Simakova (Записки Горного института)
Numerous local varieties of weathering crusts are known in the South Timan. They differ in their position in the section, type of weathering products, substrates, and occurrence. The aim of the research is to identify patterns in the distribution of rock-forming, rare and rare earth elements and the composition of clay minerals in clay formations of the weathering crusts. The main task is to describe the occurrence and geochemical features that enable determining the genetic type and formation conditions of weathering crusts. The paper presents the results of a study of the distribution of petrogenic, rare earth, rare elements, and clay minerals in weathering crust of different ages, genetic types and occurrence conditions on the Dzhezhimparma Ridge and the Nemskaya Upland in the South Timan. We found that hydromica-kaolinite-type weathering crust is developed after the Late Riphean Dzhezhim Fm. rocks in the basement-cover contact zone on the Dzhezhimparma Upland, and the layer of fine-grained rock at the base of the Devonian section previously considered a weathering crust was formed as a result of mechanical destruction of the Devonian sandstones during movement in the thrust zone. In the Vadyavozh quarry located on the Nemskaya Upland, we studied and described the formations of Mesozoic-Cenozoic areal and linear weathering crusts after the Late Riphean Dzhezhim Fm. rocks. We found that micaceous siltstones in the siltstone-sandstone strata of the Dzhezhim Fm. are associated with the Riphean stage of crust formation and are composed of weathering crust material redeposited in the epicontinental basin.